2021
DOI: 10.11591/ijphs.v10i4.21053
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and public health practices during lockdown towards COVID-19 in Bangladesh

Abstract: The study aimed to assess the role of having knowledge and essential hygiene practices to prevent coronavirus pandemic and to find out the relationship between people’s knowledge and good hygiene practices with socio-demographic variables during coronavirus disease 2019 (COVID-19) pandemic situation. In this study, data were collected from 248 respondents for cross-sectional study using voluntary response sampling from April, 30 2020 to May, 30 2020, during lockdown situation in Bangladesh. Descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…45.9% of senior citizens felt that the main source of coronavirus information came from family members than from electronic media (36%). One study in Bangladesh found that about 49% of respondents had received information about COVID-19 from the internet [16].…”
Section: Knowledge About Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…45.9% of senior citizens felt that the main source of coronavirus information came from family members than from electronic media (36%). One study in Bangladesh found that about 49% of respondents had received information about COVID-19 from the internet [16].…”
Section: Knowledge About Covid-19mentioning
confidence: 99%
“…61.9% of males and 48.7% of females visited their friends or relatives face to face whereas 57.1% of males and 45.3% of females changed their eating habits since the spread of coronavirus. One study in Bangladesh found that more than 71% of the respondents had followed stay at home, 22.98% were confused about these preventive measures and only 5.65% agreed that staying at home cannot reduce the spread of COVID -19 [16]. Italian older were more likely to engage in preventative measures than young [17].…”
Section: Knowledge About Preventive Measuresmentioning
confidence: 99%